Formal preparation of regioregular and alternating thiophene–thiophene copolymers bearing different substituents - Mori, Atsunori; Fujita, Keisuke; Kubota, Chihiro; Suzuki, Toyoko; Okano, Kentaro; Matsumoto, Takuya; Nishino, Takashi; Horie, Masaki (Beilstein Journal of Organic Chemistry, 2020)
Differently substituted thiophene–thiophene-alternating copolymers were formally synthesized employing a halo-bithiophene as a monomer. Nickel-catalyzed polymerization of bithiophene with substituents at the 3-position, including alkyl-, fluoroalkyl-, or oligosiloxane-containing groups, afforded the corresponding copolymers in good to excellent yield. The solubility test in organic solvents was performed to reveal that several copolymers showed a superior solubility. X-ray diffraction analysis of the thin film of the alternating copolymers composed of methyl and branched oligosiloxane substituents was also performed, and the results suggested the formation of a dual-layered film structure.
Keywords: alternating copolymer; nickel(II) catalyst; oligosiloxane; regioregular polythiophene; solubility